SALES OF JAPANESE SIM CARDS AT PT. ADVENTURE TRAVEL GROUP - Anna Yuliani Pratiwi (WIDAI Japanese Journal, 2020)
As times progressed, communication and information became rapidly evolving. One of the media used is a mobile phone. Nowadays, especially on vacation abroad, we can't get off the phone. Therefore, a SIM card is created for overseas. At this time, a large number of people who need internet facilities abroad. One of the travel agents opened a special brand SIM Card, to meet the needs of its customers. This makes traveling more practical. In this Final Task report, the author discusses "Japan SIM Card Sales at PT. Adventure Travel Group". In the technique of drafting reports, the authors use descriptive methods that describe actual, factual, and systematic arrangements. The authors also conduct live observations in the field, collect company data, and discussions with company staff related to the report. From the results of fieldwork practices, the authors concluded that the providers that became mainstays are Softbank and Docomo. The process of resale of Japanese SIM Card requires thoroughness and good cooperation between staff, ranging from equipment preparation until product resale on the sales site. Advantages of purchasing Japanese SIM Card at PT. Adventure Travel Group is Auto Active and usea the best providers. The disadvantages of buying Japanese SIM card in Japan is impractical, more expensive, and troublesome.